2020
DOI: 10.3920/wmj2019.2449
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of mycotoxins in stored maize: case study of Shandong, China

Abstract: Risk characterisation of dietary exposure of aflatoxins (AFs), fumonisins (FBs), deoxynivalenol (DON), zearalenone (ZEA) in maize from Shandong Province was conducted in this study. A total of 520 maize samples were collected after harvesting in 2014 and 2015 from 26 selected villages in Shandong Province, China. A deterministic approach was used in the current study. The dietary intake data of maize was obtained from ‘Shandong Statistical Yearbook 2018’. The risk characterisation of FBs, DON, and ZEA was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…The incidence of AFB1 and aFs in corn samples in our study (58% and 71%, respectively) is comparable to the results from Serbia [ 33 , 35 , 56 ] given in Table 4 , while in other studies, a lower incidence was reported [ 4 , 38 , 39 , 43 , 45 , 47 , 48 , 49 , 52 , 53 , 54 ]. In Croatia, Slovenia, Romania, the EU, Egypt, China, the Middle East, and African countries, it was 0–45.4% [ 4 , 38 , 39 , 43 , 45 , 47 , 48 , 49 , 52 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The incidence of AFB1 and aFs in corn samples in our study (58% and 71%, respectively) is comparable to the results from Serbia [ 33 , 35 , 56 ] given in Table 4 , while in other studies, a lower incidence was reported [ 4 , 38 , 39 , 43 , 45 , 47 , 48 , 49 , 52 , 53 , 54 ]. In Croatia, Slovenia, Romania, the EU, Egypt, China, the Middle East, and African countries, it was 0–45.4% [ 4 , 38 , 39 , 43 , 45 , 47 , 48 , 49 , 52 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 89%
“…The incidence of AFB1 and aFs in corn samples in our study (58% and 71%, respectively) is comparable to the results from Serbia [33,35,56] given in Table 4, while in other studies, a lower incidence was reported [4,38,39,43,45,[47][48][49][52][53][54]. In Croatia, Slovenia, Romania, the EU, Egypt, China, the Middle East, and African countries, it was 0-45.4% [4,38,39,43,45,[47][48][49][52][53][54]. In a global survey on the occurrence of mycotoxins in feed performed in 100 countries, an AFB1 incidence of 24% was reported [48], while Lee and Ryu [60] reported a 55% incidence for aFs based on global occurrence data reported from 2006 to 2016.…”
Section: Comparison With the Incidence Of Afs From Other Countriessupporting
confidence: 89%
See 1 more Smart Citation
“…The estimated liver cancer risk of 0.038 and 0.23 cancers/year/100,000 population and 0.018 and 0.19 cancers/year/100,000 population was reported for children and adults at mean and high consumption level, respectively, which is lower than China's current liver cancer incidence i.e., 24.6 cases per 100,000 per year. Therefore, a low health risk was concluded (Dong et al, 2020). Similarly, in spite of the lower MOEs (<100), a total diet risk assessment by Zhang et al (2020) suggested a low risk of liver cancer for the population of Guangzhou, China as the estimated risk of liver cancer (0.0264 cancers/year/100,000 population) was lower than China's liver cancer incidence i.e.…”
Section: Cereals and Cereal Productsmentioning
confidence: 99%
“…The risk of human exposure to multiple mycotoxins raised a growing concern about their potential impact on human health. Dong et al (2020) characterised the risk of dietary exposure of aflatoxins, fumonisins (FBs), DON and zearalenone (ZEN) in maize from the Shandong province. Evaluation of mycotoxins in 520 maize samples showed that the average concentration did not exceed the Chinese regulatory limit, although the incidences of each mycotoxin in maize were high.…”
Section: Risk Assessment Associated With Multiple Mycotoxins Exposurementioning
confidence: 99%